Usia penyapihan dan hubungannya dengan intelegensi pada siswa TK - Hesti Purwandari; Endy Paryanto Prawirohartono; Sri Hartati (Jurnal Gizi Klinik Indonesia, 2008)
Background: Nutrition is the important aspect in improving quality of human being resources. Malnutrition is still a problem in Indonesia. This problem is caused by some factors, those are direct and indirect factors. Direct factors consist of dietary intake and infection disease. Dietary intake is a combination of breast milk and complementary foods. Indirect factors consist of food supply at home, treatment of pregnant mother and children, and health service. Early weaning will generate malnutrition at young age if it is not complemented with sufficient feeding. Malnutrition at young age can affect brain function permanently, because the development of brain will be optimum before two years old. This condition can influence the development of chidren’s intelligence.Objective: The objective of the study was to find out the relationship between weaning age and intelligence.Method: This was a cross sectional study, at kindergarten in Mlati Sub-district. Subjects were recruited based on a simple random sampling technique. There were 194 children and mothers who met the inclusion criteria and the exclusion criteria. Those were who had chronic disease and never got breastfeeding. Instruments in this study were questionnaire, microtoise, and Standford-Binet test. Data were analysed with chi square test.Results: The study showed that 52.6% of children had the age of weaning <2 years and 47.4% had weaning at >2 years. Out of 194 children, 79.9% were normal and 20.1% of them were stunted. There were 97.7% of children who had good intelligence, whereas 2.1% of them had low intelligence. There was no significant relationship between nutritional status and intelligence (p=0.181), but there was significant relationship between cognitive stimulation and intelligence (p=0.037). There was no significant relationship between weaning age and nutritional status (p=0.209), and neither was relationship between weaning age and intelligence (p=1.000).Conclusion: There was no significant relationship between nutritional status and intelligence.